(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Like other languages, Bangla has some phonetically distinct letters that make it difficult for young children to learn and pronounce. As a result, they make mistakes in the articulation of those letters. Results from earlier studies suggest that phonemes that are similar in sound become confusing for each other in short-term memory, which can create a barrier for learning and retention in long-term memory. However, any comprehensive study of the distinctive features of the Bangla alphabet has yet to be carried out. The goal of the current study was to determine whether there are any differences between the two independent groups’ levels of learning and working memory (the training/experimental group, which received training in phonetic distinctive features, and the non-training/control group, which received no training). Children between seven and eight years of age were selected as participants in the study. The result of this experiment shows a clear connection between distinctive feature training and articulation. Specific training in some alphabet letters in Bangla helps the children in their letter learning and working memory. For children with articulation problems, distinctive feature training can bring about significant developments in terms of the number of errors and sound precision. Dhaka Univ. J. Biol. Sci. 32(2): 257-263, 2023 (July)